1983
DOI: 10.1530/acta.0.1020521
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical hyperthyroidism - a graded condition

Abstract: In 65 consecutive surgical patients with multinodular goitre and with preclinical hyperthyroidism (TRH-resistant suppression of TSH in the presence of normal circulating thyroid hormones) the individual values of the FT4-index (FT4-I) and FT3-index (FT3-I) showed a wide range form low normal to high normal with mean values not differing from those in TRH\x=req-\ responsive goitre patients and from controls. Thirty-five patients underwent repeated pre-operative TRH tests: 11 (group A) were TRH-unresponsive on o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

1983
1983
1991
1991

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 6 publications
1
8
0
Order By: Relevance
“…The results of the present study help to define the thyroid status of patients with normal T3 and T4 but blunted TSH response to TRH. As was the case in some other studies (Kirkegaard et al, 1977;Smeulers et al, 1977;Elte et al, 1978;Morgans et al, 1978;Bianchi et al, 1979;Kallner & Ljunggren, 1979;Langer et al, 1979;Kirkegaard et a/., 1980;Gemsenjager & Girard, 1983), we detected no significant difference between the basal thyroid hormone levels (T3, T4. free T4) of these patients and ofcontrols.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The results of the present study help to define the thyroid status of patients with normal T3 and T4 but blunted TSH response to TRH. As was the case in some other studies (Kirkegaard et al, 1977;Smeulers et al, 1977;Elte et al, 1978;Morgans et al, 1978;Bianchi et al, 1979;Kallner & Ljunggren, 1979;Langer et al, 1979;Kirkegaard et a/., 1980;Gemsenjager & Girard, 1983), we detected no significant difference between the basal thyroid hormone levels (T3, T4. free T4) of these patients and ofcontrols.…”
Section: Discussionsupporting
confidence: 82%
“…Moreover, TRH responsiveness is recovered following partial thyroidectorny (Gemsenjager et ai., 1976;Blichert-Toff et af., 1978;Gemsenjager & Girard, 1983) or improved after propranolol treatment (Elte et al, 1982). Metabolic studies (Staub et af., 1980;Tortosa et al, 1984), however have failed to reveal evidence of hyperthyroidism in these patients.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In both these studies, lowering of the L-thyroxine dose resulted in normalization of TSH and correction of previously hyperthyroid tissue function. Gemsenjager and Girard (1983) reported that patients who were TRH unresponsive on one occasion may prove to be responsive on subsequent testing without any change in free thyroid hormone indices. Vermiglio et al (1987) described a patient with paroxysmal supraventricular tachycardia who had episodic increases in free thyroid hormone levels, coincident with bouts of tachycardia, the TSH response to TRH being suppressed.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with autonomous nodules it has been considered that high normal T3 levels may be the cause of a suppressed TSH response to TRH and may represent the development of thyrotoxicosis (Hamburger, 1980). Gemsenjager and Girard (1983) suggested the observed TSH suppression in such patients may be due to episodic hypersecretion of thyroid hormones.…”
Section: S U M M a R Ymentioning
confidence: 99%